Pengembangan Media Pembelajaran Peace Generation Game dalam Meningkatkan Wawasan Kebangsaan Global pada Mahasiswa IISIP YAPIS Biak Papua - Patma Tuasikal; Jelita Purnamasari; Rahmah Agustiani (Lembag, 2025)
The low level of nationalism knowledge has led to the prominence of autonomous region implementation concerning the status of local people, low social concern, increased religious symbolism, rising acts of violence, and social disharmony, which have become serious issues in society. The aim of this research is to produce the Peace Generation Games Learning Media to enhance global nationalism awareness among students at IISIP Yapis Biak Papua. The research uses the development model from Borg and Gall, which includes planning, product design, product validation, product trials, and final product. The validation showed no need for revision. The trial was conducted on students by measuring their accuracy in answering questions during the game within a 5-second duration to assess their knowledge of global nationalism. The average result of the Peace Generation Games without revisions shows that 20 students completed the game successfully. Based on the results, it can be concluded that this learning media is valid, practical, and effective, thus improving the learning process in enhancing global nationalism awareness among students.